Management of Human Resources (HR) to Move MSMEs in the Digital Era in Marga Mulya Village Districts, Bekasi City - Heni Rohaeni Rohaeni; Novita Wahyu; Murti Wijayanti; Alloysius Harry Mukti; Ika Sunayah (Jurnal Pengabdian Masyarakat Formosa, 2023)
Management of human resources as an MSME driver deserves to be done immediately, this is because it is very useful for the sustainability of an MSME, especially in the Digital 4.0 era, currently human resources as drivers are required to have the ability to use digital marketing to market their products. One of the MSME areas with creative business potential that can support the economy of the surrounding residents is Marga Mulya Village, North Bekasi District, Bekasi City. This study aims to find out how big the role of HR management is in driving and managing MSMEs in this digital era to utilize technological advances in this digital era to maximize the sales of the products they produce. Mastering technology is a skill that is needed in business management. If the ability to master technology can be achieved, the performance of MSMEs, especially in terms of marketing, can increase because we know that MSMEs are one type of business that has great potential in Indonesia